Pushto-Pārsi-Āsyāyī w̄ranī - Binava, Abdu̲l Raouf (Da Afghnistān da ʻUl̄mo Akademī, da Zhabo aw Adab̌yato Markaz, Pushto Tolanah, 1983)
On the development of elegiac poetry in Afghanistan in the Persian, Pushto, and Sanskrit languages; includes samples of poems, some translated into Pushto from Sanskrit.